Legal Certainty of Guarantor for the Existence of Foreign Investors in Indonesia - I Made Rusdiko; I Ketut Widia; I Wayan Rideng (Jurnal Hukum Prasada, 2019)
One of the effects of globalization is the development of an increasingly complex investment scope, among others, the emergence of certain Foreign Investors who set up companies in Indonesia with management status and full ownership by these investors. This has obscured the provisions regarding guarantors for their existence in the Indonesian Territory as stipulated in Law No. 6 of 2011 concerning Immigration. The Law on Limited Liability Companies and the Investment Law, does not provide a regulation regarding the obligation of the existence of Indonesian Citizens in the management of companies established by foreigners who have been guarantors. The formulation of the problem to be examined is: how is the legal certainty of the guarantor and who can be the guarantor for the existence of the foreign investor in obtaining a residence permit in Indonesia. This type of research is normative legal research because of the absence of norms, referring to Article 63 paragraph (1) of Law Number 6 Year 2011 concerning Immigration. Based on the results of the study concluded that there has been a vacuum of norms regarding guarantors for certain foreign investors in obtaining guarantors that guarantee their existence in the Territory of Indonesia. This causes legal uncertainty for the guarantor and the investor in obtaining a residence permit. Therefore it is necessary to deregulate existing laws and regulations so that the guarantor and investors get legal certainty and protection while they are in the territory of Indonesia.